2013
DOI: 10.1186/1471-2393-13-58
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder analysis for a maternal and newborn health project in Eastern Uganda

Abstract: BackgroundBased on the realization that Uganda is not on track to achieving Millennium Development Goals 4 and 5, Makerere University School of Public Health in collaboration with other partners proposed to conduct two community based maternal/newborn care interventions aimed at increasing access to health facility care through transport vouchers and use of community health workers to promote ideal family care practices. Prior to the implementation, a stakeholder analysis was undertaken to assess and map stake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 25 publications
1
41
0
Order By: Relevance
“…The importance of stakeholders engagement in design and selection of interventions is also highlighted in other studies [ 49 51 ]. Similar to these studies we found the investment in long-term and extensive stakeholders involvement very appropriate for the design and selection of interventions as it enhanced ownership, which is crucial for successful and sustainable integration of the intervention in the system [ 24 , 49 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 94%
“…The importance of stakeholders engagement in design and selection of interventions is also highlighted in other studies [ 49 51 ]. Similar to these studies we found the investment in long-term and extensive stakeholders involvement very appropriate for the design and selection of interventions as it enhanced ownership, which is crucial for successful and sustainable integration of the intervention in the system [ 24 , 49 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 94%
“…For SROI stage 1 (Establishing scope and identifying key stakeholders), we conducted a review of the literature,18 and a brainstorming session with programme staff to preidentify stakeholders. These were subsequently purposively sampled, asked to confirm their role and used to identify additional stakeholders (snowballing).…”
Section: Methodsmentioning
confidence: 99%
“…Review of the domestic literature showed that the published studies mostly describe the rate, causes and risk factors of the neonatal mortality in a cross-sectional manner (6)(7)(8)(9)(10)(11) and no study was available as policy analysis of neonatal mortality in Iran. The search of the international literature resulted in some papers on policies of reducing the neonatal mortality in some countries but they were limited in number and also limited to a particular aspect of the policy process such as agenda setting or stakeholder analysis (12)(13)(14)(15). Thus no comprehensive study was found that had performed a policy analysis on reducing neonatal mortality considering all areas and steps of policy process.…”
Section: Figure1mentioning
confidence: 99%